Discovery of a Lead Brain‐Penetrating Gonadotropin‐Releasing Hormone Receptor Antagonist with Saturable Binding in Brain. (10th August 2020) - Bekker, Roberto B. W.; Fjellaksel, Richard; Hjornevik, Trine; Nuruddin, Syed; Rafique, Waqas; Hansen, Jørn H.; Sundset, Rune; Haraldsen, Ira H.; Riss, Patrick J.
Abstract: We report the synthesis, radiosynthesis and biological characterisation of two gonadotropin‐releasing hormone receptor (GnRH−R) antagonists with nanomolar binding affinity. A small library of GnRH−R antagonists was synthesised in 20–67 % overall yield with the aim of identifying a high‐affinity antagonist capable of crossing the blood–brain barrier. Binding affinity to rat GnRH−R was determined by autoradiography in competitive‐binding studies against [ 125 I]buserelin, and inhibition constants were calculated by using the Cheng–Prusoff equation. The radioligands were obtained in 46–79 % radiochemical yield and >95 % purity and with a molar activity of 19–38 MBq/nmol by direct nucleophilic radiofluorination. Positron emission tomography imaging in rat under baseline conditions in comparison to pretreatment with a receptor‐saturating dose of GnRH antagonist revealed saturable uptake (0.1 %ID/mL) into the brain. Abstract : Hot‐flashes light the path to hormone receptor functions in brain : Two novel GnRH PET radioligands have been developed and tested in rat brain tissue. For the first time, a ligand, [ 18 F]4, shows concentration‐dependent, saturable binding combined with saturable uptake into the brain. On this basis, the development of PET radiotracers for GnRH imaging in the brain becomes feasible.